Practical Approach of Environmental Awareness to Broadening Community Participation: A Case Study of Pindad (Persero) - Dewi Permatasari; Trianto Sutrisno; Zen Wahyudin (Journal of Management Practices, Humanities and Social Sciences, 2020)
The purpose of this study is to discuss the activity in the manufacturing industry, consisting of energy efficiency and responsible resource consumption to reduce waste emitted to the environment, taking into account the life cycle thinking. Manufacturing industries, both in commercial and strategic defense sectors are in trends to start their changing paradigm on environmental management. PT Pindad (Persero) as one of national manufacturing industry in Indonesia has been initiated related programs for the last few years. Starting year of 2020, the industry have implemented new transformation on energy and environmental preservation program, which also simultaneously conducted in community development area. This paper has collected both primary and secondary data depending upon onsite data availability. Data is obtained in several related divisions that responsible to do monitoring periodically. Therefore, range of data used in this paper started from 2018 onwards. Results shows that life cycle thinking of the Weapons Division consist of Design, Development, Manufacture, and Assembling activity, have potential impact in wastewater toxicity and air emission. This impact somehow drives the industry to reports the improvement program comprehensively, mainly in manufacturing area. Moreover, in the same objectives to spread environmental concern, the industry also conducted ex-situ conservation and land rehabilitation, while also develop awareness on environmental, safety, and health aspect to the long-run community empowerment.